Modified endoscopic ultrasound-guided double-balloon-occluded gastroenterostomy bypass (M-EPASS): a pilot study - Marino, Amanda; Bessissow, Ali; Miller, Corey; Valenti, David; Boucher, Louis; Chaudhury, Prosanto; Barkun, Jeffrey; Forbes, Nauzer; Khashab, Mouen A.; Martel, Myriam; Chen, Yen-I (Endoscopy, 2021)
Introduction We recently developed a double-balloon device, using widely available existing technology, to facilitate endoscopic ultrasound-guided gastroenterostomy (EUS-GE). Our aim is to assess the feasibility of this modified approach to EUS-guided double-balloon-occluded gastroenterostomy bypass (M-EPASS).Methods This was a single-center retrospective study of consecutive patients undergoing M-EPASS from January 2019 to August 2020. The double-balloon device consists of two vascular balloons that optimize the distension of a targeted small-bowel segment for EUS-guided stent insertion. The primary end point was the rate of technical success. Results 11 patients (45 % women; mean [standard deviation (SD)] age 64.9 [8.6]) with malignant gastric outlet obstruction were included. Technical and clinical success (ability to tolerate an oral diet) were achieved in 91 % (10/11) and 80 % (8/10) of patients, respectively. There was one adverse event (9 %) due to stent migration. Two patients (18 %) required re-intervention for stent obstruction secondary to food impaction. The mean (SD) time to a low residue diet was 3.5 (2.4) days. Conclusion M-EPASS appears to facilitate the technique of EUS-GE, potentially enhancing its safety and clinical adoption. Larger studies are needed to validate this innovative approach to gastric outlet obstruction.